PENGARUH CAPITAL ADEQUANCY RATIO (CAR), NON PERFORMING FINANCING (NPF) TERHADAP PEMBIAYAAN MURABAHAH PADA BANK SYARIAH MANDIRI INDONESIA TAHUN 2013 -2022 - Ervin Mardalena; Noviansyah; Dahlia (Ekonomika, 2025)
This research is motivated by a phenomenon that is not in accordance with theory, where if Capital Adequacy Ratio increases then Murâbaḥah Financing will also increase, and vice versa if Murâbaḥah Financing decreases then Capital Adequacy Ratio decreases. Then, if the Non Performing Financing increases, Murâbaḥah Financing decreases, and vice versa, if Murâbaḥah Financing increases, the Non Performing Financing decreases. However, it can be seen from the data that it does not match the theory.The formulation of the problemin this research is whe ther there is a simultaneous and partial influence of Capital Adequacy Ratio and Non Performing Financing on Murâbaḥah Financing. The aim of this research is to find out how much influence the Capital Adequacy Ratio and Non Performing Financing variables simultaneously and partially have on Murâbaḥah Financing. The theory used in this research is the theory of Capital Adequacy Ratio, Non-Performing Finance and Murâbaḥah Financing. The minimum Capital Adequacy Ratio set by the Bank for International Settlement (BIS) is 8%. And in Bank Indonesia regulation Number 15/2/PBI/2013 it is stated that the maximum Non Performing Financing value is 5%. This research is a multiple regression analysis with a quantitative research type and a descriptive approach with secondary data and a sample of 48. The data comes from monthly published financial reports on Sharia Commercial Banks in Indonesia for 2013-2022 which are published by the Financial Services Authority via the website www.ojk.go.id. The results of the partial research (t test) state that, Capital Adequacy Ratio has no effect on Murâbaḥah Financing, there is an influence of Non Performing Financing on Murâbaḥah Financing. Simultaneous research results (Test F) state that CAR and NPF simultaneously have a positive and significant influence on Murâbaḥah Financing. Mean while,there sult sof the coefficientof determination (R2) of CAR and Non Performing Financing influence Murâbaḥah Financingby 79.6%. The remaining20.4%is influenced by other factors or variables not included in this research.